Appendices - Baruch, Adele (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2019)
Appendix A presents a further discussion of methodology as it relates to both the Courage and Moral Choice Project (CMPC) and the Zakynthos and Hurricane Katrina interviews and analyses. Appendix B contains the interview questions. Appendix C presents a curriculum map for those interested in undertaking a project similar to the CMCP.